Mysteriously Meant The Rediscovery of Pagan Symbolism and Allegorical Interpretation in the Renaissance - Allen, Don Cameron (Johns Hopkins University Press, 1971)
In Mysteriously Meant, Professor Allen maps the intellectual landscape of the Renaissance as he explains the discovery of an allegorical interpretation of Greek, Latin, and finally Egyptian myths and the effect this discovery had on the development of modern attitudes toward myth. He believes that to understand Renaissance literature one must understand the interpretations of classical myth known to the sixteenth and seventeenth centuries. In unraveling the elusive strands of myth, allegory, and symbol from the fabric of Renaissance literature such as Milton's Paradise Lost, Allen is a helpful guide. His discussion of Renaissance authors is as authoritative as it is inclusive. His empathy with the scholars of the Renaissance keeps his discussion lively-a witty study of interpreters of mythography from the past.